2023
DOI: 10.1097/mco.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional regulation of hepatic de novo lipogenesis in humans

Abstract: Purpose of reviewDe novo lipogenesis (DNL) is a metabolic process occurring mainly within the liver, in humans. Insulin is a primary signal for promoting DNL; thus, nutritional state is a key determinant for upregulation of the pathway. However, the effects of dietary macronutrient composition on hepatic DNL remain unclear. Nor is it clear if a nutrition-induced increase in DNL results in accumulation of intra-hepatic triglyceride (IHTG); a mechanism often proposed for pathological IHTG. Here, we review the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Elevated hepatic de novo lipogenesis, a process in which the liver synthesizes fatty acids from dietary carbohydrates and proteins, is among the earliest metabolic abnormalities related to insulin resistance and fatty liver disease [ 35 ]. In this context, we observed that semaglutide led to a reduction in intrahepatic TG content and de novo lipogenesis, as evidenced by decreased levels of de novo lipogenesis end products, such as lipotoxic fatty acids (palmitic, palmitoleic and oleic acids) and the downregulation of lipogenic enzymes (Acaca, Fasn and Scd1).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated hepatic de novo lipogenesis, a process in which the liver synthesizes fatty acids from dietary carbohydrates and proteins, is among the earliest metabolic abnormalities related to insulin resistance and fatty liver disease [ 35 ]. In this context, we observed that semaglutide led to a reduction in intrahepatic TG content and de novo lipogenesis, as evidenced by decreased levels of de novo lipogenesis end products, such as lipotoxic fatty acids (palmitic, palmitoleic and oleic acids) and the downregulation of lipogenic enzymes (Acaca, Fasn and Scd1).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the replacement of a daily carbohydrate portion with 200 gr of brassicaceous vegetables improves the circulating biomarkers linked to NAFLD, the FLI, and the FibroScan score. These results are explained by sugar restriction, which both downregulate the de novo lipogenesis (DNL) widely recognized in NAFLD [ 28 , 29 ] and reduce inflammatory responses [ 30 ]. Furthermore, our findings support recent research showing an inverse relationship between leafy green vegetable consumption and NAFLD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of fish oil has been shown to both prevent and reverse IFALD in premature infants [45], and in some reports to improve IFALD in adults. These effects may relate to the impact of long chain n-3 PUFAs on hepatic lipid metabolism as also discussed by Cross et al [2].…”
mentioning
confidence: 84%
“…Despite decades of research, much remains to be learned about fatty acid and complex lipid metabolism in humans and its regulation. Cross et al [2] provide an update on regulation of de novo lipogenesis (DNL; synthesis of fatty acids and their accumulation into triglycerides) which mainly occurs in the liver. They also review the experimental techniques that can be used to assess DNL in humans.…”
mentioning
confidence: 99%